1976
DOI: 10.1113/jphysiol.1976.sp011497
|View full text |Cite
|
Sign up to set email alerts
|

Caudate stimulation and substantia nigra activity in the rat.

Abstract: SUMMARY1. The responses of spontaneously active single neurones in the substantia nigra and overlying mesencephalic reticular formation have been analysed during the electrical stimulation of the ipsilateral caudate nucleus. Experiments were performed in rats anaesthetized with urethane or pentobarbitone. All recordings were made extracellularly with multibarrelled glass micropipsttes which were also used to test neuronal responsiveness to electrophoretically administered substances. The micropipette tip posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

1977
1977
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(38 citation statements)
references
References 40 publications
8
30
0
Order By: Relevance
“…24 However, when a higher stimulus intensity (>500 ”A) was used, dopaminergic neurons were inhibited, 24 consistent with the majority of reports on the effects of striatal stimulation on identified dopaminergic neurons. 15,16,29,37,38,42,50,52 Since the stimulus parameters used in the present study were 1.0 mA with a duration of 500 ”s, the stimulus would be expected to inhibit, not excite, dopaminergic neurons, and is thus unlikely to account for the failure to detect any silent dopaminergic neurons.…”
Section: Silent Dopaminergic Neurons Were Not Observed In Control Ratsmentioning
confidence: 96%
“…24 However, when a higher stimulus intensity (>500 ”A) was used, dopaminergic neurons were inhibited, 24 consistent with the majority of reports on the effects of striatal stimulation on identified dopaminergic neurons. 15,16,29,37,38,42,50,52 Since the stimulus parameters used in the present study were 1.0 mA with a duration of 500 ”s, the stimulus would be expected to inhibit, not excite, dopaminergic neurons, and is thus unlikely to account for the failure to detect any silent dopaminergic neurons.…”
Section: Silent Dopaminergic Neurons Were Not Observed In Control Ratsmentioning
confidence: 96%
“…The present results are in agreement with the inhibition by GABAB receptors of the nigral dopaminergic activity, since baclofen infusion into the SN decreased the release of '** dopamine in the SN. It has been reported that intranigral injection of GABA decreases dopamine release in the ipsilateral ST (Reid et al, 1988), while nigral perfusion of baclofen (10 JM) decreases dopamine release in the same SN 150 180 210 and in the ipsilateral ST (Westerink et al, 1992 (Aghajanian & Bunney, 1975;Dray et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…To this end an examination was made of the effects of tetanus toxin on the inhibitory effect of striatal stimulation on neurones in the substantia nigra. Electrophysiological and neurochemical data indicates that this pathway is relatively long and that the inhibitory effect of striatal stimulation is mediated by GABA or a GABA-like substance (Frigyesi & Purpura, 1967;Feltz, 1971;Precht & Yoshida, 1971;Crossman, Walker & Woodruff, 1973;Fonnum, Grofova, Rinvik, Storm-Mathisen & Walberg, 1974;Dray, Gonye & Oakley, 1976). …”
Section: Introductionmentioning
confidence: 99%